Penanaman Nilai-Nilai Sosial melalui Program Edukasi Stop Anti Bullying pada Anak Usia Dini di Taman Kanak-Kanak - Pujiastuti, Gunarti Retnoningrum; Alawiyah, Syarifah; Afifah, Aulya Nur; Andini, Mutiara; Nurfajriah, Yayah; Azahra, Azizah; Ala, Faridatul' (Pakis Journal Institute, 2026)
Bullying in early childhood is a social problem that requires serious attention because it can affect children's psychological and social development. Children at this age are in the character formation stage, so it is important to instill social values ​​from an early age. This community service activity aims to instill social values ​​through the Stop Anti-Bullying education program at Bani Adam Kindergarten, Jakasetia Village. The method used is a qualitative descriptive approach with participatory education through fun activities that are appropriate to the characteristics of early childhood, such as singing, storytelling, question and answer, social behavior simulations, and coloring activities on anti-bullying-themed LKPD (Learning Worksheet). Evaluation was carried out through observations of children's participation, responses, and changes in attitudes and initial behavior during the activity. The results of the activity showed an increase in children's understanding of bullying behavior and good social behavior. Children began to show empathy, dare to apologize, help friends, and use polite language in interactions. The Stop Anti-Bullying education program has a positive impact as an effort to prevent bullying from an early age and helps create a safe, comfortable, and child-friendly learning environment.